1994
DOI: 10.1149/1.2055056
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Impurity Metal Ions in Electrolytic Manganese Dioxide

Abstract: The amounts of impurity metal ions incorporated into electrolytic manganese dioxide (EMD) during its preparation were measured as a function of metal ion concentrations and current densities. The amount of incorporated ions increased in proportion to the concentration in solution and at a fixed concentration it was different from ion to ion: Ni 2. < Zn 2. < Co 2. < Cu z* < Fe 3. < Pb 2+. The specific surface area of the formed EMD was larger for impurity ions with higher incorporation affinity. Further, the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 1 publication
0
9
0
1
Order By: Relevance
“…Today it is used in alkaline primary and secondary batteries. The reversibility of this cell as being a major bottleneck, most of the Zn-MnO 2 work has focused on incorporating metal oxides additives to manganese dioxide in order to make this cell rechargeable [12][13][14][15][16][17][18][19]. EMD is one of the widely used cathode materials for alkaline batteries, lithium manganese primary batteries.…”
Section: Introductionmentioning
confidence: 99%
“…Today it is used in alkaline primary and secondary batteries. The reversibility of this cell as being a major bottleneck, most of the Zn-MnO 2 work has focused on incorporating metal oxides additives to manganese dioxide in order to make this cell rechargeable [12][13][14][15][16][17][18][19]. EMD is one of the widely used cathode materials for alkaline batteries, lithium manganese primary batteries.…”
Section: Introductionmentioning
confidence: 99%
“…As was commented upon previously, when there is no convection reaction (8) between MnOOH and Fe 2þ ions may be predominant. However, the fact that the decrease of current in Fig.…”
Section: Glassy Carbon Electrode In Mnso 4 Solutions Containing Fe 2þmentioning
confidence: 70%
“…Paul and Cartwright [7] analysed the deposition of MnO 2 in a disk and ring system in the presence of ferrous ions, and they found that the deposit can be corroded by reduction with ferrous ions at electrode potentials that seem sufficiently positive to protect the manganese oxide deposit anodically. Tamura et al [8] have studied the incorporation of metallic ion impurities, and have found that Fe 3þ ions are incorporated into the crystalline structure of the EMD, and the resulting material presents good behaviour during discharge. Elsherief [9] discussed some aspects of electroleaching of MnO 2 ore with sulphuric acid and found that the presence of ferrous ion greatly increased the speed of the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…These factors resulted in a larger surface area with a porous nature, as discussed in Section 2.1. For the chosen bivalent Ni 2+ or Co 2+ dopants, the effect of nucleation rate promotes the adsorption of these ions, owing to their activity in adsorption . Together, the doped EMD materials have been successfully electrodeposited with improved physicochemical characteristics from the smaller particle sizes that enable their use as electrodes in rechargeable alkaline batteries.…”
Section: Resultsmentioning
confidence: 99%